CRITICAL DISCOURSE ANALYSIS OF FILM THE PEAKY BLINDERS - Sigit Surahman; Manda Shinta Bella; Ignasius Liliek Senaharjanta; Rully Rully (Universitas Bunda Mulia, 2023)
Film as a communication medium is audio-visual which is used to deliver messages to audiences. This article aims to explain the linguistic space for discourse on social phenomena in post-war I and II through the audio-visual medium The Peaky Blinders film in relation to the emergence of discriminatory discourse on social status among the lower class people, namely ex-soldiers workers. The critical paradigm is used as a perspective in this article. The results that have been analyzed by the author are that social inequality has an impact, namely the existence of social hegemony and power takes place when the grassroots including the proletariat have accepted and imitated the way of life, way of thinking, and views of the elite group that dominates and exploits them and causes some discrimination, namely such as discrimination of a profession or position, discrimination of clothing, and discrimination of behavior or manners.